g-C3N4 for Photocatalytic Degradation of Parabens: Precursors Influence, the Radiation Source and Simultaneous Ozonation Evaluation - Fernandes, Eryk (2023)
Graphitic carbon nitride (g-C3N4) is a promising catalyst for contaminants of emerging concern removal applications, especially as a visible-light-driven material. In this study, g-C3N4 catalysts were effectively synthesized through a simple thermal polymerization method, using melamine, urea, and thiourea as precursors to elucidate the influence of these compounds on the final product’s photocatalytic performance. The degradation of a mixture of three parabens was investigated under different types of radiation: two artificial, ultraviolet-A (UVA) and visible LED, and natural sunlight. The urea-based catalyst (UCN) presented better results under all radiation sources, followed by thiourea, and finally, melamine. Among the artificial light sources, the degradation of parabens under UVA was considerably higher than visible—up to 51% and 21%, respectively—using UCN; however, the broader spectrum of natural sunlight was able to achieve the highest removals, up to 92%, using UCN. Comparing artificial radiation sources, UVA lamps presented 45% lower energy consumption and associated costs. Photocatalytic ozonation was tested using UCN and MCN, with UCN once more possessing superior performance and a synergetic effect between photocatalysis and ozonation, with complete removal under 12 min. The use of g-C3N4 was then successfully tested in initial screening and found to be an efficient alternative in more low-cost and feasible solar photocatalysis water treatment.